An isolated intestinal duplication cyst masquerading as a mucinous cystic neoplasm of the pancreas: A case report and review of the literature. (2017) - Weitman, Evan; Al Diffalha, Sameer; Centeno, Barbara; Hodul, Pamela
Highlights: Intestinal duplications cysts are rare congenital anomalies that can occur throughout the gastrointestinal tract. Isolated intestinal duplication cysts can present with vague abdominal complaints. Diagnosis can be challenging even with imaging. Our clinical workup was suggestive of a mucinous cystic neoplasm (MCN) of the pancreas. This represents the first reported case of an enteric duplication cyst that mimicked an MCN of the pancreas. Abstract: Introduction: Enteric duplication cysts presenting in adulthood are rare. Isolated enteric duplication cysts, which lack a connection to the GI tract or the adjacent mesenteric vasculature, have only been cited in six previous case reports. Case presentation: A 48-year-old female presented with a four-year history of intermittent nausea, vomiting and abdominal pain. Computed tomography (CT) scan of the abdomen revealed a 7 cm multi-lobular, calcified, cystic lesion intimately involved with the pancreas. Endoscopic ultrasound (EUS)-guided fine-needle aspiration (FNA) was non-diagnostic; however, the cyst fluid Carcinoembryonic Antigen (CEA) level was significantly elevated leading to a presumed diagnosis of a mucinous cystic neoplasm (MCN) of the pancreas. Intraoperatively, the cystic mass was identified and notably did not have any true attachments to the neighboring pancreas, gastrointestinal tract or vasculature. Final pathology demonstrated an isolated small bowel duplication cyst. Discussion: In this case a patient presented with a clinical picture consistent with an MCN of the pancreas. However, intraoperatively and on final pathology the mass was found to be an isolated enteric duplication cyst. This represents only the seventh such case report in an adult. Conclusion: Although rare, isolated enteric duplication cysts can be considered in a patient presenting with chronic abdominal pain and an abdominal mass on imaging. In this case we demonstrate that an isolated enteric duplication cyst can clinically mimic an MCN of the pancreas.